Mapping the ‘home’: A literature review on Filipino migration and diaspora - Pacoma, Marc Agon (Jurnal Studi Komunikasi, 2020)
This article aimed to present a comprehensive literature review on Philippine migration and diaspora. Diaspora is not a new concept for Filipinos; they have been constantly connected to migration, one of the interconnected aspects of the global workforce. Diaspora and migration as common household terms can be traced back from the first overseas Filipino farmworkers in Hawaii in the middle of 1900s to the presently relocated skilled workers and domestic helpers in the Middle East countries and various Asian countries. The author intended to provide a better understanding of existing researches and debates on the topic and evaluate their relationship with the current research study. More so, the essay was intended to identify the research gaps arising from previous scholarly writings, which was beneficial to the author as he embarks in research on Filipino migration and diaspora. Research gaps serve several purposes for the possible direction of future research projects. Most of the literature focused on the reasons of migration; migration narratives and experiences; homeland media consumption; the role of digital technologies and social media in fostering transnational families’ relationships and reinforcing migrant workers’ national and cultural identities. In terms of the approaches, participant observation, interview and digital ethnography were the employed research methodologies.